USING PELLETS, AN ECO ALTERNATIVE - Iosif TEMPEA; Diana Nicoleta BRĂNICĂ (Fiabilitate şi Durabilitate)
Pallets are obtained in specialized factories, generally through extrusion, and additives, binders or any other additional chemical substances are not necessary, duet o the naturally existent resins in the basic raw material.